Factors associated with perceived health of school-aged children in rural Rwanda: an opportunity to leverage community health workers to enhance school health promotion and primary healthcare systems linkages - Anatole Manzi; Daniel Nguyen; Benjamin Katz; Clara Agyapomaa Michel; Theophile Nilingiyimana; Titien Sendarasi; Joseph Niyonzima; Olive Nyiraneza; Norbert Blaise Bimenyimana; Elizabeth Bloom (BMC Primary Care, 2024)
Abstract Background In many low-income countries, enhancing the health of school-aged children is often impeded by insufficient or limited knowledge regarding their health status. Further, hands-on health promotion interventions are nearly non-existent due to the lack of designated health workers. The disconnection between schools and primary care facilities further exacerbates this issue. To address these challenges, the World Health Organization has introduced the Health Promoting School (HPS) framework, a comprehensive model designed to integrate health into all aspects of school life and promote physical, mental, and social well-being. We sought to assess the perceived health status of school-aged children, identify associated factors, and explore the role of community health workers (CHWs) in public schools in rural Rwanda. Methods We carried out a convergent mixed methods study among teachers and community members in rural areas of Musanze, Rwanda. Data collection instruments were adapted from the World Health Organization’s HPS framework and the literature. We conducted six in-depth interviews and three focus group discussions. We performed a logistic regression analysis to examine the factors associated with perceived health. Thematic analysis was used to analyze the qualitative data. Results A total of 479 individuals participated in this survey. Of these, 425 (89%) were community members, while 54 (11%) were employed as teachers at Nyabirehe or Rwinzovu public schools. Almost half of respondents 221 (46%) described the children’s health as poor. Many factors were associated with perceived children’s health, including having an established leadership team for school-based health promotion (OR = 1.97, 95%CI: 1.01,3,84), and being familiar with school-based health promotion (OR = 4.77, 95%CI: 2.27,10.0). Qualitative results described the CHW as a bridge between communities, schools, and primary healthcare centers. Conclusion This study revealed that the health of schoolchildren needs particular attention. In resource-limited settings, HPS presents a promising opportunity to address the health and well-being of children at rural public schools. However, adapted policies, the establishment of health promotion teams, and hands-on orientation for teachers and community members are necessary to ensure an effective implementation of HPS. In Rwanda and other low-income countries where public schools lack nursing staff, CHWs could play a vital role in enhancing HPS and the linkage between schools and primary healthcare facilities.